Synthesis and properties of new derivatives of 4h-1,2,4-oxadiazin-5(6H)-one - Turmanov, R.; Alimkhan, B.; Kanzhar, S.; Zhussupova, L.; Togyzbayeva, N. (Edelweiss Applied Science and Technology, 2025)
This paper presents an improved method for the synthesis of new derivatives of 4H-1,2,4-oxadiazine-5(6H)-one, which are an important class of heterocyclic compounds with wide potential for use in medical and pharmaceutical chemistry. The synthesis was carried out based on the interaction of (Z)-N'-hydroxy-4-methylbenzimide and (Z)-N'-hydroxy-5-methylthiophene-2-carboxymidide with a number of methyl and ethyl-halogen derivatives of carboxylic acids. The study found that the use of sodium tert-butylate in dimethyl sulfoxide at room temperature provides effective cyclization with the formation of target products with yields of up to 76%. It was revealed that the effect of substituents in the aromatic or heterocyclic fragment of the original amidoximes does not have a significant effect on reactivity, which confirms the universality of the proposed approach. All synthesized compounds were characterized by modern analysis methods, including NMR (1H, 13C) and high-resolution mass spectrometry (HRMS), which fully confirmed their structure and purity. The developed method is characterized by mild conditions, ease of execution, and environmental friendliness, as it does not require the use of toxic reagents or metal catalysts.